Life cycle of chokka-squid Loligo reynaudii in South African waters. Issue 4 (2nd December 2016) - Lipiński, MR; van der Vyver, JSF; Shaw, P; Sauer, WHH
Abstract : This short note summarises past and current knowledge of the life cycle of chokka-squid Loligo reynaudii d'Orbigny, 1845, in South African waters. Prior to approximately 2010, the chokka-squid stock was considered simple and uniform, with one paralarval pool, the drift of paralarvae westwards, one main nursery area and one main, long spawning migration of adult squid eastwards, back to the main spawning grounds. Based on new information, this life-history scheme has been revised. Genetically, the stock is uniform; however, morphologically, it comprises three main geographic groups. It is proposed that the differences between the groups originate from many different paralarval events and that short (not long) migrations dominate the life cycle.